THE IMPACT OF MASS MEDIA ON VALUE SYSTEM FORMATION DURING WARTIME - Rosina Petrovna SHEVCHENKO; Kateryna Anatolyivna TOMAK (Psihologie, 2024)
The article examines the influence of mass media on the formation of individual value systems in the context of the modern world. The authors argue that media products can significantly impact the formation and development of personal values. A total of 45 respondents, aged from 20 to 50 years old, took part in the study, divided into three age groups of 15 people each: the first group of 20-30 years old, the second group of 30-40 years old, the third group of 40-50 years old. Statistical analysis of the data revealed significant differences in the evaluation of values such as health, communication, kindness, love, social status, and leadership, based on age (p < 0.01). The findings confirm the hypothesis that the media products consumed by individuals influence their value systems, particularly during wartime conditions.